RISK OF THROMBOEMBOLISM IN CHRONIC KIDNEY DISEASE PATIENTS WITH NON VALVULAR ATRIAL FIBRILLATION : A SYSTEMATIC REVIEW - Anggunawan, Sulfadli; Zainal, Sri Hikmawaty (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Individuals with CKD are at higher risk for thromboembolic events than those without CKD whilst also at a higher bleeding risk. NVAF often coexist with CKD and heightens the risk of one another. This study aimed to investigate the risk of thromboembolism in CKD patients with NVAF. Methods: This systematic review used Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 as standards. Inclusion criteria for literature eligibility are full-text literature, written in english, and published between 2014 and 2024. Exclusion criteria used for this study were editorials, review articles and identical journal that has been published, and submissions without DOI. Literatures were collected from online reference sources like Pubmed and SagePub. Result: In the PubMed database, the results of our search brought up 45 articles, whereas the results of our search on SagePub brought up 382 articles. The results of the search conducted for the last year of 2014 yielded a total 10 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 5 papers, 3 of which came from PubMed and 2 of which came from SagePub. We included five research that met the criteria. Conclusion:  The existence of both NVAF and CKD increase the risk of thromboembolic events. There are various modalities to analyze the risk of thromboembolism by assessing risk scores, kidney function, and utilizing transesophageal echocardiography (TEE). In order to prevent ischaemic stroke in NVAF patients, anticoagulants can be administered by in consideration to the kidney function.